Transarterial radioembolization with Iodine-131-Lipiodol for hepatic metastases from gastrointestinal malignancies – Experience in tertiary care oncology center in India - Vidya Bhargavi (South Asian Journal of Cancer, 2019)
Context: Unresectable colorectal hepatic metastases can be treated with radioembolization. Aims: The aim of this study is to analyze the response and survival benefits of transarterial radioembolization (TARE) with Iodine-131 (131I) Lipiodol for hepatic metastases from gastrointestinal malignancies. Settings and Design: Retrospective study of 20 patients with pathologically proven hepatic metastases from primary gastrointestinal malignancies referred for palliative therapy with TARE. Subjects and Methods: At baseline, standard laboratory and imaging data were recorded. All patients fulfilling the inclusion/exclusion criteria underwent TARE with 131I Lipiodol. Post procedure, the patients were reviewed after 1 month with follow-up positron emission tomography–computed tomography and tumor marker levels to evaluate treatment response with continued follow-up till December 2016 and overall survival calculated. Statistical Analysis Used: Data were analyzed using a statistical analysis package (Social sciences, version 15.0 for Windows; SSPS Inc.). Survival data were plotted using Kaplan–Meier survival curves. Results: At the end of follow-up period, 15 of 20 patients were alive. The mean and median survival was 38.88 ± 5.0 months (95% confidence interval [CI], 29.03–48.74 months, P = 0.17) and 49.3 ± 12.4 months (95% CI, 25.0–73.7 months, P = 0.17), respectively. 66 months survival was 75%. Response evaluation in 10 patients showed partial response in 3 (30%), stable disease in 2 (20%) and progressive disease in 5 (50%) patients. All patients with partial response showed a reduction in serum tumor marker levels. Conclusions: TARE with 131I-Lipiodol is highly effective with a significant survival benefit in refractory cases of hepatic metastases from gastrointestinal malignancies.